Nanopore sensing at ultra-low concentrations using single-molecule dielectrophoretic trapping - Freedman, Kevin J.; Otto, Lauren M.; Ivanov, Aleksandar P.; Barik, Avijit; Oh, Sang-Hyun; Edel, Joshua B. (Nature communications, 2016)
Single-molecule techniques are being developed with the exciting prospect of revolutionizing the healthcare industry by generating vast amounts of genetic and proteomic data. One exceptionally promising route is in the use of nanopore sensors. However, a well-known complexity is that detection and capture is predominantly diffusion limited. This problem is compounded when taking into account the capture volume of a nanopore, typically 10 8 –10 10 times smaller than the sample volume. To rectify this disproportionate ratio, we demonstrate a simple, yet powerful, method based on coupling single-molecule dielectrophoretic trapping to nanopore sensing. We show that DNA can be captured from a controllable, but typically much larger, volume and concentrated at the tip of a metallic nanopore. This enables the detection of single molecules at concentrations as low as 5 fM, which is approximately a 10 3 reduction in the limit of detection compared with existing methods, while still maintaining efficient throughput. Nanopore sensors have shown tremendous potential for biomolecule sensing, though the diffusion-controlled capture can limit the speed of analysis. Here, the authors report a dielectrophoretic method to concentrate DNA near the tip of a nanopore, reducing the limit of detection by three orders of magnitude.